REKONSTRUKSI EPISTEMOLOGI TAFSIR MAQASHIDI DALAM MERESPONS KRISIS KEMANUSIAAN KONTEMPORER - agung rifat; Nurul Waliyah Hayatunnida (Eduvis : Jurnal Manajemen Pendidikan Islam, 2026)
Contemporary humanitarian crises encompassing climate change, forced displacement, social inequality, and biotechnological ethical dilemmas increasingly demand that Islamic scholarship offer coherent, contextually grounded, and morally authoritative responses that transcend the limitations of classical textual interpretation. This study investigates the epistemological reconstruction of maqashidi tafsir as a methodological framework for responding to contemporary humanitarian crises, pursuing three specific objectives (1) to analyze the epistemological foundations and developmental trajectory of maqashidi tafsir as a distinct hermeneutical approach within Islamic thought, (2) to identify the principal epistemological limitations of classical tafsir methodologies in addressing the complexity and urgency of contemporary humanitarian crises, and (3) to formulate a reconstructed epistemological framework for maqashidi tafsir that enables generative, justice-oriented, and contextually responsive interpretations of the Quran in confronting contemporary humanitarian challenges. Employing a systematic library research methodology drawing on thirty-five peer-reviewed sources published between 2020 and 2025, the study proposes the Reconstructive Maqashidi Hermeneutics Framework (RMHF), a five-dimensional interpretive model integrating classical maqashid theory with contemporary humanitarian ethics.